INCREASING INSIGHTS OF ELEMENTARY SCHOOL STUDENTS ON THE IMPLEMENTATION OF THE WASTE AWARENESS MOVEMENT - Muliawan, I Komang; Putri, Dewa Ayu Putu Adhiya Garini; Wardana Sudarta, Abe Pramuda; Pradila Samita, Gede Aldian; Esta Hendrawan, I Putu Agus (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
This activity aims to provide knowledge to students about waste and its impact on the environment, especially at State Elementary Schools 3 Riang Gede. The background of this activity is the main problem that exists, namely waste. This problem must be overcome from an early age so that the mindset or mindset of the community is formed regarding the bad effects of waste. The method used is a direct approach to the people of Riang Gede Village, the main targets of this project are students at State Elementary Schools 3 Riang Gede. This location was chosen because the children of State Elementary Schools 3 Riang Gede mostly come from Riang Gede Village, so it is hoped that in the future the children will be able to transmit the habits in the family environment. After this activity was carried out, it can be concluded that the students at State Elementary Schools 3 Riang Gede have the intention to know more about what waste is and its uses as evidenced by their work in the form of handicrafts made from waste. From this activity, the hope is that it can provide useful knowledge about the bad impact of waste and can increase awareness from an early age as well as creative products produced in the process of utilizing waste, especially plastic waste which has a high selling value.